Protective behavior during the second wave of the COVID-19 pandemic in Denmark - Jørgensen, Frederik Juhl; Petersen, Michael Bang (Politica, 2022)
A fundamental aim during the COVID-19 pandemic has been to motivate comprehensive behavioral change in the population in order to protect them against infection with the corona virus. Here, we study how psychological factors relate to such behavior change during the second wave of the pandemic. Using survey data representative of the adult Danish population, we demonstrate that people who (1) perceive the coronavirus as a personal threat, (2) perceive that behavior change makes a difference (“response efficacy”), (3) perceive that behavior change does not come with high costs (“response costs”), and (4) have high institutional trust are more willing to comply with health-protective behavioral advice. Furthermore, we show that the factors (2)-(4) mute the association between personal threat and protective behavior. Thus, we identify a psychological path without fear to foster behavior change during a pandemic.